2021
DOI: 10.1161/strokeaha.121.034601
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Stroke Hospital Care During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: Background and Purpose: We systematically evaluated the impact of the coronavirus 2019 (COVID-19) pandemic on stroke care across the world. Methods: Observational studies comparing characteristics, acute treatment delivery, or hospitalization outcomes between patients with stroke admitted during the COVID-19 pandemic and those admitted before the pandemic were identified by Medline, Scopus, and Embase databases search. Random-effects meta-analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 91 publications
2
36
1
Order By: Relevance
“…This was a multicenter cohort study aimed at describing the differences in clinical characteristics and outcomes of patients with acute The COVID-19 pandemic changed the clinical profile of patients with acute stroke, with an increased prevalence of younger patients and more severe strokes attributed to large vessel occlusions and higher in-hospital mortality compared with pre-COVID controls [20]. Our study shows no changes in the demographic and risk factor profile between the first two waves, but lower stroke severity and in-hospital mortality in the second wave.…”
Section: Discussionmentioning
confidence: 99%
“…This was a multicenter cohort study aimed at describing the differences in clinical characteristics and outcomes of patients with acute The COVID-19 pandemic changed the clinical profile of patients with acute stroke, with an increased prevalence of younger patients and more severe strokes attributed to large vessel occlusions and higher in-hospital mortality compared with pre-COVID controls [20]. Our study shows no changes in the demographic and risk factor profile between the first two waves, but lower stroke severity and in-hospital mortality in the second wave.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been declines in absolute numbers of patients treated with reperfusion therapies for acute ischemic stroke, the relative proportion of patients treated with EVT has risen. A recent meta-analysis of 46 observational cohort studies (including 129,491 patients) reported a 24% increase in the odds of EVT during pandemic months when compared to a prior control period [ 48 ]. This is likely, at least in part, explained by the higher proportion of patients having more severe strokes at presentation [ 7 ], with a 63% higher odds of having a large vessel occlusion [ 48 ].…”
Section: Management Paradigmsmentioning
confidence: 99%
“…Younger age may be a reflection of those without recognized, or yet diagnosed, traditional vascular risk factors for AIS having neurological symptoms and complications (such as AIS) from COVID-19; however, positivity status and medical history are not collected in this database. A recent systematic review and meta-analysis revealed increased proportions of younger patients and severe strokes attributed to a LVO but also noted that higher rates of undiagnosed and thus untreated atrial fibrillation following regional lockdowns were seen and could be an explanation for younger age [ 18 ]. This apprehension to go outside and possibly contracting COVID-19 could also skew the population as older patients with more risk factors may have stayed home and not sought emergent care despite stroke symptoms.…”
Section: Discussionmentioning
confidence: 99%